THE IMPORTANCE OF EARLY ERYTHEMATOUS REACTION IN PURIFIED PROTEIN DERIVATIVE SKIN TESTING - (:unkn) unknown (ROYAL SOC MEDICINE SERVICES LTD, 1994)
We attempted to assess the diagnostic value of the early erythematous reaction observed at the sixth hour after the application of purified protein derivative (PPD) skin testing. For this purpose, 64 children with pulmonary tuberculosis and 49 healthy age-matched controls were PPD skin tested. Our results showed that the erythematous reaction of 5 mm or greater at the sixth hour was able to detect patients with active tuberculosis with 76% sensitivity, 85% specificity, 87% positive predictivity and 73% negative predictivity. Among 113 subjects, 6h erythematous reaction of 5 mm or greater in size had 83% sensitivity to detect the ones who subsequently developed 10 mm or greater induration reaction at 48 h. We concluded that the sixth hour early erythematous reaction is just as helpful as the 48h induration of 10 mm or greater in detecting patients with pulmonary tuberculosis.